The Role of Monitoring Spatio-Temporal Change in Achieving Resilience of the Suburban Landscape. - Athanasiadou, Eleni A.; Tratsela, Maria (Springer Fachmedien, 2017)
A City is a constructed landscape which epitomizes human intelligence and creativity, depicts social, cultural and economic development and still remains the most favorable and important habitat for the human species. Cities continue to grow, yet covering only about 3% of the earth's surface, causing major negative impacts to the environment such as the natural resources depletion, carbon emissions, pollution of ground water, etc. A resilient City is a flexible, adaptable to change organism which comes in a form of equilibrium to meet quality criteria of living. Change is always reflected in form. The hypothesis of this study is whether monitoring of spatio-temporal landscape change is an important method in examining landscape resilience. It focuses mainly an the notions of transformation, time and process using the principles of landscape ecology, in order to capture the way a landscape may respond to environmental, social and economic change. A relative research presented hereby was conducted between 2010 and 2012 and included the study of the spatio-temporal change in the suburban landscape east of the city of Thessaloniki, an area of approximately 10 K hectares. Results demonstrated change in LULC patterns of thirteen different land use/cover types and the transformation of a once arable agricultural landscape into a suburban landscape with mixed residential and agricultural uses. Socio-economic and ecological factors influenced this drastic change in structure and function of the landscape in study. The study concludes that monitoring spatio-temporal landscape change contributes in examining the potentially of a landscape towards resilience.
Keywords: Stadtregion; Stadtumland; Transformation; Landnutzung; Flächennutzung; Nutzungsänderung; Landwirtschaftliche Nutzfläche; Suburbanisierung; Verstädterung; Monitoring; Resilienz